Decisions at the Boundary: Role Choice and Alliance Manager Behaviors. (April 2017) - Luvison, Dave; Cummings, Jeffrey L.
Individuals in a firm tend to operate within a unifying set of organizational role expectations, but this is rarely the case in strategic alliances where different organizations' interests and expectations are involved. In this conceptual article, we consider how alliance managers (AMs), the boundary spanners responsible for alliance success, navigate receiving firm-sent role expectations while also receiving legitimate partner-sent expectations. Role theory is incomplete regarding how AMs cope with this increasingly common, mixed-motive context and how the pull of the focal firm on AMs is affected. We address this theory gap by conceptualizing how the limiting nature of firm-sent expectations is affected by AMs' receipt of legitimate partner-sent roles, and is moderated by AMs' entrepreneurism and the structure of the interfirm collaborative environment.